6n+5(-6n+1)=173

Simple and best practice solution for 6n+5(-6n+1)=173 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6n+5(-6n+1)=173 equation:



6n+5(-6n+1)=173
We move all terms to the left:
6n+5(-6n+1)-(173)=0
We multiply parentheses
6n-30n+5-173=0
We add all the numbers together, and all the variables
-24n-168=0
We move all terms containing n to the left, all other terms to the right
-24n=168
n=168/-24
n=-7

See similar equations:

| 3(u-4)-8u=-17 | | 78+v=-15 | | 7x22x7=90 | | 6.9−2.8x=30.986. | | x−4=16 | | 0.1+x=20.5 | | 5x-2+2x=12 | | 8-(-h)=1 | | 25=c+20 | | w-12+8=12 | | 17=8v | | 2(-3x+4)-2x=4(-2x+6) | | -1.4+u/3=-8.9 | | 14=y12 | | 0.15(3n+2)+0.05=0.5(0.9+0.7) | | 20x+11=22x-1 | | -12w+8=12 | | 0.15(3n+2)+0.005=0.5(0.9+0.7) | | 150x-75+130x-93=80x-152x | | V=(28-2x)(16-2x)x | | 7+5y=6y | | -10+5x+95+40=180 | | 8(x-1)-2x=-2(1+x)+5x | | 3/4(8x+12)=-2x+65 | | 5x-8+2x+7+4x-1=180 | | 6(7+g)+5g=42 | | 4(x–2)=16 | | ⅖(10x-15)=10x+10 | | -7.1=x/7+4.1 | | 2(2x+3)=4(x+1.4)+.1 | | -16t=56t=t | | -6x+6=-10+2x |

Equations solver categories